PENINGKATAN PEMAHAMAN SISWA SMK BANGUN PERSADA TENTANG PERNIKAHAN DINI - Fransiska Novita Eleanora; Edy Supriyanto; Sarton Sinambela; Rona Apriana Fajarwati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Early marriage or marriage at a young age is very prevalent among adolescents, where the occurrence of marriage is due to various factors of low access to education for children, quality of health services from reproduction, especially for girls who are lacking, there is no opportunity in the economic field , the existence of free association and also because of poverty, besides that marriage at this young age has a negative impact which can cause divorce, domestic violence, severe depression, the emergence of child labor, economic hardship and hampered education. Early marriage is a violation of children's rights, especially the right to live and grow and develop. This service activity provides an understanding of the impact of early marriage. Meanwhile, the aim is that students and students can understand the efforts to prevent early marriage in the aspects of marriage and child protection Keywords: early marriage; enhancement; prevention; adolescents;